Dynamics of the Thermal Environment in Climate-Controlled Poultry Houses for Broiler Chickens - Jacqueline Cardoso Ferreira; Alessandro Torres Campos; Patrícia Ferreira Ponciano Ferraz; Marcelo Bahuti; Tadayuki Yanagi Junior; Joaquim Paulo da Silva; Sílvia Costa Ferreira (AgriEngineering)
The implementation of poultry houses with enhanced control over environmental variables represents a solution to the growing demands for production and animal welfare. This study assessed the internal environment of dark-house poultry houses for broilers on a weekly basis throughout a production cycle. Data were collected over six weeks, from March to April 2016 involving 40,000 Cobb500TM broilers. A Hobo® datalogger continuously monitored the temperature (°C), relative humidity (%), dew point temperature (°C), and black globe temperature (°C) at 15 min intervals. The indices analyzed included the temperature and humidity index (THI), the black globe and humidity index (BGHI), and enthalpy (H). In the first week, both the THI and BGHI indicated favorable conditions for the birds, with the THI ranging from 72.4 to 80 and the BGHI from 77 to 81.6. Between the second and fifth weeks, the THI conditions varied between thermal comfort and discomfort, from 56.6 to 72. In the sixth week, all indices indicated discomfort, reflecting increased metabolism and population density. The dark-house system demonstrated a feed efficiency of 51%, an accumulated mortality rate of 1.97%, and a total production of 99,873 kg of meat. The study highlights the importance of continuously monitoring and adjusting environmental conditions to optimize production and enhance bird welfare.